Strategic Role of Principals in Islamic Digital-Based Human Resource Management - Zarkasi; Raziki Waldan; Fachrurazi (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the strategic role of Islamic digital leadership in human resource management at SMK Mandiri Pontianak, focusing on innovation and technological adaptation. A qualitative approach was employed, with data collected through in-depth interviews with the principal, vice principals, and IT staff. The findings reveal that the principal integrates Islamic values such as amanah (trustworthiness), musyawarah (deliberation), and ihsan (excellence) into digital leadership practices to strengthen governance, internal communication, and decision-making processes. The use of digital platforms—such as academic information systems and collaborative applications—is aimed at efficiency and reflects values of transparency, justice, and collective responsibility within the ethical framework of Islamic leadership. A participatory and innovative school culture is fostered through online teacher training and promoting spiritually grounded, technology-based learning practices. Challenges such as limited infrastructure and digital skill gaps are addressed through ukhuwah (Islamic solidarity)  manifested in peer support systems, such as more tech-savvy teachers assisting others, and communal sharing of digital devices. Capacity building was conducted through periodic in-house training, digital literacy workshops, and one-on-one mentoring, with post-training surveys indicating that 85% of teachers and 78% of administrative staff experienced improved digital performance. Moral and material support included the provision of internet quotas, recognition for innovative teachers, and spiritual motivation through Islamic-themed digital leadership meetings. The novelty of this study lies in the systematic integration of Islamic values into digital leadership practices within the vocational education context, expanding the application of transformational and distributed leadership theories through an Islamic lens. This research contributes to developing an Islamic value-based digital leadership model in vocational schools.